HPV16 viral characteristics in primary, recurrent and metastatic vulvar carcinoma - Lillsunde Larsson, Gabriella; Kaliff, Malin; Sorbe, Bengt; Helenius, Gisela; Karlsson, Mats G. (Papillomavirus research, 2018)
Vulvar carcinoma is the fourth most common gynecological malignancy. Two separate carcinogenic pathways are suggested, where one is associated with the human papillomavirus (HPV) and HPV16 the most common genotype. The aim of this study was to evaluate HPV-markers in a set of primary tumors, metastases and recurrent lesions of vulvar squamous cell carcinomas (VSCC). Ten HPV16-positive VSCC with metastatic regional lymph nodes, distant lymphoid/hematogenous metastases or local recurrent lesions were investigated for HPV genotype, HPV16 variant, HPV16 viral load, HPV16 integration and HPV16 E2BS3 and 4 methylation. In all 10 analyzed case series, the same HPV genotype (HPV16), HPV16 variant and level of viral load were detected in all lesions within a patient case. Primary tumors with a high E2/E6 ratio were found to have fewer vulvar recurrences and/or metastases after diagnosis and treatment. Also, a significantly lower viral load was evident in regional lymph nodes compared to primary tumors. The data presented strengthens the evidence for a clonal HPV-induced pathway for vulvar carcinoma